2005
DOI: 10.1126/science.1109557
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor H Polymorphism in Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a major cause of blindness in the elderly. We report a genome-wide screen of 96 cases and 50 controls for polymorphisms associated with AMD. Among 116,204 single-nucleotide polymorphisms genotyped, an intronic and common variant in the complement factor H gene (CFH) is strongly associated with AMD (nominal P value <10(-7)). In individuals homozygous for the risk allele, the likelihood of AMD is increased by a factor of 7.4 (95% confidence interval 2.9 to 19). Resequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

47
2,611
8
36

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 3,948 publications
(2,754 citation statements)
references
References 30 publications
47
2,611
8
36
Order By: Relevance
“…Recent evidence suggests that CFH may play a significant role in the pathogenesis of AMD. [8][9][10][11] CFH is a single polypeptide chain with a molecular weight of 155 kD that is present in the plasma at a concentration of 110-615 mg/ml. It is constitutively produced by the liver.…”
Section: Complement Factor Hmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that CFH may play a significant role in the pathogenesis of AMD. [8][9][10][11] CFH is a single polypeptide chain with a molecular weight of 155 kD that is present in the plasma at a concentration of 110-615 mg/ml. It is constitutively produced by the liver.…”
Section: Complement Factor Hmentioning
confidence: 99%
“…6 Recent studies have also identified multiple genetic variants of Complement factor H (CFH), a regulator protein that can confer elevated risk of AMD. [8][9][10][11] The complement system…”
Section: Introductionmentioning
confidence: 99%
“…The mutations are composed of a coding SNP (rs10490924) that produces the A69S mutation in the putative Age‐Related Maculopathy Susceptibility 2 (ARMS2) gene, an insertion–deletion del443ins54 that deletes the polyadenylation signal sequences of the RNA transcript, and the SNP, rs11200638, in the promoter of High Temperature Requirement A Serine Peptidase 1 ( HTRA1 ; Yang et al., 2006). The other major genetic locus linked to AMD is at chromosome 1q31, where a single nucleotide polymorphism (SNP) rs1061170 causes a missense mutation Y402H in complement factor H (CFH; Edwards et al., 2005; Klein et al., 2005; Hageman et al., 2005; Haines et al., 2005). These two genetic loci, 1q31 and 10q26, were the first to be identified in human GWAS, and they confer the most significant genetic risk of AMD alleles.…”
Section: Introductionmentioning
confidence: 99%
“…These two genetic loci, 1q31 and 10q26, were the first to be identified in human GWAS, and they confer the most significant genetic risk of AMD alleles. The initial cohort studies showed the risk of developing AMD was 4.6 times that of wild type among people heterozygous and 7.4 times increased for those homozygous for the CFH risk allele (Klein et al., 2005). Those heterozygous for the ARMS2/HTRA1 risk allele were at ~2.7 times greater risk of AMD, whereas homozygotes had 8.2 times increased risk (Rivera et al., 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of the important role that genetic background plays in the pathogenesis of AMD was greatly enhanced in 2005, with several independent reports associating the complement factor H (CFH) gene, located on chromosome 1q31, with this disease (Edwards et al, 2005;Hageman et al, 2005;Haines et al, 2005;Klein et al, 2005). The strong association of the CFH Y402H variant allele with increased risk for AMD suggested an important role for the alternative complement pathway and the involvement of inflammation in the pathogenesis of AMD (Anderson et al, 2002;Hageman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%